2021
DOI: 10.3390/ijerph18115826
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Exercise Progression in an Australian Cardiac Rehabilitation Program: Should Cardiac Intervention, Age, or Physical Capacity Be Considered?

Abstract: Progression of prescribed exercise is important to facilitate attainment of optimal physical capacity during cardiac rehabilitation. However, it is not clear how often exercise is progressed or to what extent. This study evaluated whether exercise progression during clinical cardiac rehabilitation was different between cardiovascular treatment, age, or initial physical capacity. The prescribed exercise of sixty patients who completed 12 sessions of outpatient cardiac rehabilitation at a major Australian metrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In the Australian context, where our study found a low uptake of exercise capacity assessments, 6MWT may be a useful alternate method of assessing the functional response to CR, where mean pre–post improvement has been reported to exceed 20% in a single-centre study of 2524 CR participants 24. However, observational data from Australia suggest that exercise capacity assessments are needed in practice to accurately classify initial exercise capacity and subsequently tailor exercise prescription in CR 25…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In the Australian context, where our study found a low uptake of exercise capacity assessments, 6MWT may be a useful alternate method of assessing the functional response to CR, where mean pre–post improvement has been reported to exceed 20% in a single-centre study of 2524 CR participants 24. However, observational data from Australia suggest that exercise capacity assessments are needed in practice to accurately classify initial exercise capacity and subsequently tailor exercise prescription in CR 25…”
Section: Discussionmentioning
confidence: 75%
“… 24 However, observational data from Australia suggest that exercise capacity assessments are needed in practice to accurately classify initial exercise capacity and subsequently tailor exercise prescription in CR. 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, patients from this tennis group did not carry out physical activity because they had suffered a stroke and because there was an (external) medical prescription that indicated that exercise was essential for their recovery or to prevent the appearance of more strokes. In this regard, the CRPs carried out with guided physical exercise are effective in favouring changes towards healthy and long-lasting habits in stroke patients [5]. The fact that the tennis group presents better results than the cycle ergometer group may be due to the interest that doing an activity such as tennis outside the hospital, playing with other patients, playing for points and so forth can generate.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac rehabilitation (CR) is a programme supervised by professionals that helps people recover from heart attacks and their associated surgery [1]. It has been shown to be an effective tool for improving body composition [2,3], functional capacity and physical fitness [4][5][6], heart rate variability (HRV) [7,8] and health-related quality of life (HRQoL) [9,10]. However, and despite the unquestionable benefits provided by CRPs, a study performed in 28 European countries concluded that less than half of the cardiovascular patients benefited from a CRP [11], and, in fact, the benefits were generally transitory as patients dropped out of the programmes [12].…”
Section: Introductionmentioning
confidence: 99%